New guidelines on fitness to drive: what do they mean to psychiatrists and their patients?. (17th December 2013) - Hassab Errasoul, A.; Daly, R.
Abstract : The publication of the new guidelines is a welcome step, bringing more lucidity to the subject and providing useful guidance to clinicians. However, the guidelines pose new and unique responsibilities on mental health services with resulting training needs, resource issues and ethical issues. We propose a collaborative model based on the development of regional specialised teams to perform this task. This may prove to be a more suitable and cost effective option in the long run.